In memoriam - CPH 42(1-2) (Czasopismo Prawno-Historyczne, 1990)
Antonio Marongiu 1902-1989 (Stanislaw `Russocki) ... 205 Marian Żurowski 1923-1988 (Irena Malinowska-Kwiatkówska) ... 207 František Graus 1921-1989 (Henryk Olszewski, Klaus Zernack) ... 209